Quiet politics and business power : corporate control in Europe and Japan - Culpepper, Pepper D. (New York : Cambridge University Press, 2011)
'Does democracy control business, or does business control democracy? This study of how companies are bought and sold in four countries - France, Germany, Japan, and the Netherlands - explores this fundamental question'--Provided by publisher.
'Does democracy control business, or does business control democracy? This study of how companies are bought and sold in four countries, France, Germany, Japan, and the Netherlands, explores this fundamental question. It does so by examining variation in the rules of corporate control ,specifically, whether hostile takeovers are allowed. Takeovers have high political stakes: they result in corporate reorganizations, layoffs, and the unraveling of compromises between workers and managers. But the public rarely pays attention to issues of corporate control. As a result, political parties and legislatures are largely absent from this domain. Instead, organized managers get to make the rules, quietly drawing on their superior lobbying capacity and the deference of legislators. These tools, not campaign donations, are the true founts of managerial political influence'--Provided by publisher.
Includes bibliographical references (p. 199-213) and index.
Keywords: Corporate governance -- Europe; Corporate governance -- Japan